Development and Characterization of Folate Targeted Nanoparticle Drug Delivery System - V. V. MITTAL; S. J. PATEL; S. K. SHETH (International Journal of Pharma and Bio Sciences, 2010)
The main objective of this study was to develop and characterize tumor selective folate conjugated PEG (Polyethylene glycol) polymeric nanoparticulate system for paclitaxel delivery. Paclitaxel -loaded poly (lacticco-glycolic acid) (PLGA) nanoparticles were prepared by the solvent evaporation method and characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM) and zeta potential measurements. Result showed that preparation allowed the formation of spherical nanometric (200-300 nm), homogeneous and negatively charged particles (-23.9 mV) suitable for intravenous administration. Paclitaxel loading efficiencies were determined and release studies were performed in Tween 80 (0.1% w/v)-containing PBS at 37 °C. Prepared nanoparticles were surface modified by folate-PEG for targeting cancer cells, which is confirmed by FT-IR spectroscopy and characterized for shape, size and zeta potential measurements. The results demonstrate that folate conjugated PEG nanoparticle drug delivery system could provide increased therapeutic benefit by delivering the encapsulated drug to the folate receptor positive cancer cells.